Does the combination of citrate and phytase exudation in Nicotiana tabacum promote the acquisition of endogenous soil organic phosphorus? - Giles, Courtney D.; George, Timothy S.; Brown, Lawrie K.; Mezeli, Malika M.; Richardson, Alan E.; Shand, Charles A.; Wendler, Renate; Darch, Tegan; Menezes-Blackburn, Daniel; Cooper, Patricia; Stutter, Marc I.; Lumsdon, David G.; et al. (Plant and soil, 2017)
Background and Aims: Plant acquisition of endogenous forms of soil phosphorus (P) could reduce external P requirements in agricultural systems. This study investigated the interaction of citrate and phytase exudation in controlling the accumulation of P and depletion of soil organic P by transgenic Nicotiana tabacum plants. Methods: N. tabacum plant lines including wild-type, vector controls, transgenic plants with single-trait expression of a citrate transporter (A. thaliana frd3) or fungal phytases (phyA: A. niger, P. lycii) and crossed plant lines expressing both traits, were characterized for citrate efflux and phytase exudation. Monocultures and intercropped combinations of single-trait plants were grown in a low available P soil (12 weeks). Plant biomass, shoot P accumulation, rhizosphere soil pH and citrate-extractable-P fractions were determined. Land Equivalent Ratio and complementarity effect was determined in intercropped treatments and multiple-linearregression was used to predict shoot P accumulation based on plant exudation and soil P depletion. Results: Crossed plant lines with co-expression of citrate and phytase accumulated more shoot P than single-trait and intercropped plant treatments. Shoot P accumulation was predicted based on phytase-labile soil P, citrate efflux, and phytase activity (Rsq=0.58, P < .0001). Positive complementarity occurred between intercropped citrate-and phytase-exuding plants, with the greatest gains in shoot P occurring in plant treatments with A. niger phyA expression. Conclusions: We show for the first time that trait synergism associated with the exudation of citrate and phytase by tobacco can be linked to the improved acquisition of P and the depletion of soil organic P.